1975
DOI: 10.1148/115.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glucagon on Barium-Enema Examination

Abstract: Fifty barium-enema studies were performed with glucagon and 50 with a placebo to compare their effect on colonic spasm, patient discomfort, and diagnostic quality. Each drug was administered in a randomized double-blind fashion and was injected intramuscularly 10 minutes before beginning the enema. Bowel relaxation during fluoroscopy was graded. Patients were questioned about discomfort during and immediately after the enema, and radiographs were reviewed blindly for diagnostic quality and degree of spasm. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Whereas several studies have reported decreased discomfort and bowel spasm during and after barium enema as well as better bowel relaxation, and patient preference when glucagon is administered beforehand [16,21], the results regarding colonic distention and diagnostic accuracy are less favorable. Bova et al [21] found that the degree of colonic distention at both single-and double-contrast barium enema examination was not significantly improved by the administration of glucagon 1 mg i.v., whereas Goei et al [22] found that butyl scopolamine (Buscopan) 20 mg i.v.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Whereas several studies have reported decreased discomfort and bowel spasm during and after barium enema as well as better bowel relaxation, and patient preference when glucagon is administered beforehand [16,21], the results regarding colonic distention and diagnostic accuracy are less favorable. Bova et al [21] found that the degree of colonic distention at both single-and double-contrast barium enema examination was not significantly improved by the administration of glucagon 1 mg i.v., whereas Goei et al [22] found that butyl scopolamine (Buscopan) 20 mg i.v.…”
Section: Discussionmentioning
confidence: 96%
“…It is widely used in gastrointestinal radiology and endoscopy because of its relaxant effects on the smooth muscle of the stomach, duodenum, small bowel and colon, and its reported effectiveness and fewer side effects when compared with anticholinergic agents such as atropine, hyoscyamine, or scopolamine [14,15,16,17]. Recommendations for the minimum effective dose are 10 µg/kg intravenously, or, more practically, 0.75-1.00 mg in an adult of average weight [18].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with anticholinergic agents, glucagon at the low doses used, is virtually free of side effects, and does not interfere with transit through the small bowel [5,12,[18][19][20][21].…”
mentioning
confidence: 99%
“…Unlike the studies of the duodenum [19,20], there was little measurable difference in the diameter of the normal colon before and after the active drugs were given. The effectiveness of glucagon to relax the colon has been confirmed in further studies in patients by Meerhoff et al [34] and Harned et al [35]. Daniel et al [36] have used glucagon as an antispasmodic in the treatment of acute diverticulitis with excellent results.…”
Section: Hypotonic Colon Examinationsmentioning
confidence: 86%